(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Handicrafts have been one of the major mainstays of the Indian economy and have subsequently acquired the status of a major livelihood opportunity for a large number of women in India. Madhubani paintings are one of the oldest art forms from Mithila region of Bihar. It is known as Mithila Painting. For centuries, women from the region of Mithila have been making ritualistic paintings and expressing their own social world through the medium of paintings. This paper discusses the case and journey of a woman entrepreneur involved in madhubani paintings and other handicrafts who has not only fought out of the clutches of poverty but has also impacted the lives of sixty local women of Muzaffarpur District of Bihar. The present study aims to understand the role and potential of handicraft sector in improving and providing a sustainable livelihood option for local people especially women in the poverty ridden state of Bihar by strengthening of social capital linkages of women artisans and production in the homestead site, so that women could be economically active without leaving the home or being vulnerable to harassment or violence and empowerment of women as they learn to deal with traders. The paper also tries to identify the challenges faced by such small entrepreneurs.